THE EFFECTIVENESS OF MULTIPLE LEARNING METHODS IN ACQUIRING OFFENSIVE VOLLEYBALL SKILLS FOR STUDENTS - Asst. Dr. Maitham Razzaq Abdul Muslim; Asst. Dr. Ahmed Radhi Habib; Asst. Dr. Haider Karim Ghaidan; Asst. Dr. Ghaith Mohammed Karim (Scholars Digest Publishing, 2025)
The importance of this study stems from the researchers' endeavor to use three different teaching methods: partial, holistic, and mixed. This stems from their belief that each method has its own characteristics, both positive and negative, that influence students' learning and acquisition of motor skills. This study aims to reveal the most effective teaching method for teaching offensive volleyball skills, while taking into account the element of saving effort and time spent during the learning process. The researchers chose to adopt a variety of learning methods to improve students' learning levels and to arrive at the optimal method that contributes to optimal skill acquisition. One of the most prominent objectives of the study was to identify the differences between the results of the experimental groups in the extent of acquisition of certain offensive volleyball skills. To this end, the researchers used the experimental method with a multi-group design, as it was appropriate for the nature of the problem. The Aleppo Intermediate School for Boys was deliberately selected for the experiment. Main Conclusions: The study demonstrated that the three teaching methods have a clear impact on the acquisition of motor skills in volleyball. Understanding the finer details of the skill leads to a significant improvement in the level of learning. The blended method was superior in teaching the skills of serving and blocking, compared to the partial and complete methods.The most important recommendations are to emphasize the selection of an appropriate teaching method that is compatible with the nature of the motor performance of the skills to be learned. Rely on the blended method when teaching specific volleyball skills, as it has proven effective in improving performance.
Keywords: Learning methods, acquisition, volleyball skills.